INITIAL DESIGN OF THE STRUCTURE OF PITCHING MOTION POINT ABSORBER TYPE WAVE ENERGY CONVERTER - Rizki Ziarieputra, Muhammad
Energy demands keep on rising. To comply, the use of conventional resources of energy such as oil and coal is still the main preference. Yet, the use of these conventional resources had it problems such as a decline in resource quantity and negative environmental effect. The use of alternative renewable energy then is needed to cope with this problem. This Final Project contains the initial design of the structure of pitching motion point absorber type wave energy converter as an effort to exploit renewable energy. The scope of the study consist of calculation of performance and hydrodynamic efficiency parameter of 3 designed structure. Calculation of structure performance started with static analysis on the structure to determine its stability and continued with dynamic analysis to obtain structure response due to wave force. Structure response was then used to compose the structure performance matrix. It is obtained that all three structures have good performance at an area around the wave combination wave height of 2.5 m and a period of 3.5 seconds. Each structure performance matrix was then used to calculate the technical energy at 4 different locations with the value of significant wave height (m) and significant wave period (s) of Hs1Ts4, Hs1.5Ts6, Hs2Ts8, and Hs2Ts5 which is used to calculate the hydrodynamic efficiency parameter which is the Capture Width Ratio (CWR).